2015
DOI: 10.1007/s12035-015-9109-2
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice Overexpressing Human Angiotensin I Receptor Gene Are Susceptible to Stroke Injury

Abstract: Hypertension is one of the co-morbid conditions for stroke and profoundly increases its incidence. Angiotensin II (AngII) is shown to be at the center stage in driving the renin angiotensin system via activation of angiotensin 1 receptor (AT1R). This makes the AT1R gene one of the candidates whose differential regulation leads to the predisposition to disorders associated with hypertension. A haplotype block of four SNPs is represented primarily by haplotype-I, or Hap-I (TTAA), and haplotype-II, or Hap-II (AGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…This was associated with a protection of neurons and the blood-brain barrier, and a reduction of oxidative stress within the hippocampus (738). This finding is consistent with studies in transgenic mice overexpressing AT 1 R showing increased susceptibility to strokelike injury caused by injection of ET-1 into the striatum (426). Moreover, in the two transgenic models studied, there was a worsening of the phenotype in the model with high levels of AT 1 R expression.…”
Section: Ang II Signaling In Brain Ischemia and Strokesupporting
confidence: 85%
“…This was associated with a protection of neurons and the blood-brain barrier, and a reduction of oxidative stress within the hippocampus (738). This finding is consistent with studies in transgenic mice overexpressing AT 1 R showing increased susceptibility to strokelike injury caused by injection of ET-1 into the striatum (426). Moreover, in the two transgenic models studied, there was a worsening of the phenotype in the model with high levels of AT 1 R expression.…”
Section: Ang II Signaling In Brain Ischemia and Strokesupporting
confidence: 85%
“…It has been reported that the overexpression of ANG-1 in transgenic mice induces an increase in vascularity. Moreover, while VEGF overexpression only results in increased vascular branching, VEGF-induced vessels leak [36]. In contrast, vessels induced by ANG-1 do not leak and resist leakage induced by inflammatory agents [27].…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study, AT1R overexpression in transgenic mice strongly suppressed antioxidant activities, while enhancing brain inflammation, OS, and abnormal vascular functionality, thus leading to an increased risk of stroke-induced damage. 10 Ceolotto et al demonstrated that AT1R is expressed in higher levels in hypertensive patients carrying the A1166C CC genotype, relative to the AA or AC genotypes. 28 We, therefore, hypothesized that the AT1R polymorphisms may affect ACI susceptibility by altering AT1R levels.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 Mice that overexpress AT1R suffer from enhanced inflammatory activity, oxidative stress (OS), and abnormal vascular functionality, which leads to an increased risk of stroke-induced injury. 10 Additionally, AT1R activation also triggers atherosclerotic plaque vulnerability via modulation of the cholesterol metabolism. 11 …”
Section: Introductionmentioning
confidence: 99%